EFFECTS OF NUTRIENTS AND CROPPING DENSITY ON CASSAVA FOLIAGE IN CASSAVA-GROUNDNUT INTERCROPPING (FULafia Journal of Science and Technology, 2019)
The study was aimed at evaluating the relative effects of nutrient sources, cropping density and intercropping on selected soil variables and cassava crop foliage attributes It was conducted at Teaching and Research Farm of the Delta State University, Abraka (latitude 50 46’ and longitude 60 5’) July 2008 to June 2009, in the humid rainforest zone of Southern Nigeria. The experimental design was a 4x3x3 factorial experiment in RCBD pattern using three replicates, consisting of four nutrient levels, three cropping densities and threecropping patterns. The 4 nutrient levels were zero application, 200kg NPKMg, 40 tons of water hyacinth/poultry manure-based vermicompost (VPM) and 40 tons of water hyacinth/cow dung-based vermicompost (VCD). The 3 cropping densities were 50,000, 100,000, and 200,000 plants ha-1, while the three cropping patterns were sole groundnut, sole cassava and cassava-groundnut intercrop. Rate of leaf formation, leaf area index and stay green core of cassava were significantly increased by vermicompost application.
Keywords: cassava; leaf area index; stay green score